197k views
3 votes
-3(w+12)-11w=5 how to solve this problem

User Andwjstks
by
5.9k points

2 Answers

3 votes

Firstly, foil -3(w + 12):
-3w-36-11w=5

Next, combine like terms:
-14w-36=5

Next, add 36 on both sides of the equation:
-14w=41

Lastly, divide both sides by -14, and your answer will be
w=-(41)/(14), or approximately (rounded to the hundreths) -2.93.

4 votes


- 3w - 36 - 11w = 5

- 3w - 11w = 5 + 36

- 14w = 41

- w = (41)/(14)

w = - (41)/(14)
or

w = - 2 (13)/(14)
or

- 2.9284(4 \: d.p)

correct ne if im wrong ^-^
User Roman Pokrovskij
by
5.4k points